Changes in Structure and Reactivity of Ng2 Encapsulated in Fullerenes: A Density Functional Theory Study - Li, Meng; He, Xin; Wang, Bin; Zhao, Dongbo; Rong, Chunying; Chattaraj, Pratim K.; Liu, Shubin (Frontiers in Chemistry, 2020)
Noble gas can be no noble in certain situations from the perspective of structure, bonding and reactivity. These situations could be extreme experimental conditions or others. In this contribution, we systematically investigate the impact of fullerene encapsulation on molecular structure and chemical reactivity of noble gas dimers (Ng2) in a few fullerene molecules. To that end, we consider He2, Ne2 and Ar2 dimers encapsulated in C50, C60 and C70 fullerenes. We unveil that bond distances of Ng2 inside fullerene become substantially smaller and noble gas atoms become more electrophilic. In return, these noble gas dimers make fullerene molecules more nucleophilic. Using analytical tools from density functional theory, conceptual density functional theory, and information-theoretic approach, we appreciate the nature and origin of these structure and reactivity changes. The results and conclusions from this work should provide more new insights from the viewpoint of changing the perspectives of noble gas reactivity.